Spectroscopic confirmation of four novae in M31 - Barsukova, E.; Borisov, N.; Fabrika, S.; Sholukhova, O.; Valeev, A.; Goranskij, V.; Burwitz, V.; Pietsch, W.; Hatzidimitriou, D. (2007)
We performed spectroscopy of four optical nova candidates in M31 using the Russian 6-m telescope and the SCORPIO spectrograph. The spectral range was 380-755 nm, and the spectral resolution was 1.34 nm. M31N 2007-07b (E. Ovcharov, et al., ATel#1139): The exposure was taken between 2007 July 19.925 and 19.957 UT about 10 days after the discovery. Balmer emission lines are dominant. The value of FWHM(Halpha) corrected for instrumental profile and EW(Halpha) are 1600 km/s and -71 nm, correspondingly.
Keywords: Novae; Optical; Stars; Variables